ANALISIS DAN REKAYASA PROSES BISNIS PRODUKSI DAN DISTRIBUSI BIBIT TANAMAN - Andre Alfri Pua; Arip Mulyanto; Lillyan Hadjaratie (Diffusion: Journal of Systems and Information Technology, 2021)
Abstract In the business process of plant seeds production and distribution at Bone Bolango Watershed Management Center, there are problems in plant seeds grouping and plant seeds selection. This resulted in the distribution of plant seeds at Permanent Seedling of BPDAS-HL (Watershed and Protected Forest Management Center) of Bone Bolango was not optimal. This research aimed to determine to what extent the analysis and engineering of plant seeds production and distribution process can optimize the distribution of plant seeds at Permanent Seedling of BPDAS-HL Bone Bolango. It applied a Busness Process Improvement Analysis method. The findings showed that healthy and unhealthy plant seeds where not grouped because there was no place to classify plant seeds according to the health of the plant seeds, and there was also no dissemination about how to plant and maintain plant seeds properly and correctly. Meanwhile, the engineering camied out to Overcome this problem, namely adding a business process for the procurement of a place for grouping plant seeds according to the health of the plant seeds and dissemmation about how to plant and maintaim plant socds properly and correctly. Keywords:Plant Seeds Production and Distribution Business Process Engineering, Business Process Improvement